Green design creative, sustainable designs for the twenty-first century - Fairs, Marcus (London Carlton, 2009)
Shows how the design world is responding to the environmental challenges of the twenty-first century. This book considers the parallel issue of social sustainability, where the welfare of factory workers is given equal importance to environmental issues.
Lighting -- Homeware -- Furniture -- Textiles & materials -- Products -- Transport -- Interiors -- Architecture.
Keywords: Design -- Environmental aspects; Green products; Sustainable design; Design -- History -- 21st century; Industrial design -- History -- 21st century